„In the image and likeness” - Christian reinterpretation of the concept of a person in the perspective of the relation between God and a man in antique and medieval theology. - Wróblewska, Anna (Studia Teologiczne Białystok Drohiczyn Łomża, 2023)
Article discusses the evolution of the term “person” as a process of consecutive reinterpretations. Forming of the understanding of this definition in ancient culture, and then during dogmatic disputes can be observed as the specific re-reading of predecessors’ achievements, which enriches the teaching with new perceptions, without loosing prior content. The process exposes bidirectional influence of the way of understanding God and an human. To illustrate these changes, the author analyzes thoughts of a few selected, crucial for antiquity and middle ages thinkers.